The Design of an Ecotheology-Based Christian Religious Education Curriculum: Integrating Environmental Stewardship Values into a Love-Based Curriculum - Febrilianti Febrilianti; Misye Waliana; Eurene M Lefta; Willy Thenu; Agusthina Siahaya (MASI Mandiri Edukasi, 2026)
The global ecological crisis, reflected in deforestation, pollution, climate change, and environmental degradation, is driven not only by technological and economic factors but also by an anthropocentric worldview that regards nature merely as an object for human exploitation. This study aims to formulate a Christian Religious Education curriculum design based on ecotheology within the framework of the Love-Based Curriculum. A descriptive-analytical literature review method was employed by integrating biblical-theological foundations, educational theories, and findings from previous studies relevant to ecological education and faith formation. The analysis demonstrates that ecotheology challenges anthropocentric interpretations of Scripture and reaffirms humanity’s vocation as faithful stewards entrusted with God’s creation. At the same time, the Love-Based Curriculum broadens the understanding of Christian love by emphasizing responsibility not only toward God and fellow human beings but also toward the natural environment. The integration of these two perspectives produces a holistic curriculum that nurtures ecological faith through the development of theological understanding, environmental awareness, compassionate attitudes, and practical actions for environmental conservation. Consequently, environmental stewardship is understood as an expression of obedience to God, responsible discipleship, and tangible love for others. This curriculum model is expected to strengthen Christian education by fostering learners who demonstrate both spiritual maturity and ecological responsibility in responding to contemporary environmental challenges.